To simplify the expression \( 37 \cdot 3^{-9} \) using the properties of exponents, follow these steps:
-
Recall the property of negative exponents: \( a^{-n} = \frac{1}{a^n} \).
Applying this to \( 3^{-9} \): \[ 3^{-9} = \frac{1}{3^9} \]
-
Substitute this back into the expression: \[ 37 \cdot 3^{-9} = 37 \cdot \frac{1}{3^9} = \frac{37}{3^9} \]
-
Now, calculate \( 3^9 \): \[ 3^9 = 19683 \]
-
Substitute \( 3^9 \) back into the expression: \[ \frac{37}{3^9} = \frac{37}{19683} \]
Thus, the simplified expression with only positive exponents is: \[ \frac{37}{19683} \]
Final answer: \(\frac{37}{19683}\)